Ancient Egypt : myth and history. (Geddes & Grosset, 1997)
The religion, myths and gods of ancient Egypt explained against the background of its history, together with a comprehensive A-Z of its dynasties, rulers, historic sites and archaeological objects, from the beginning of its civilization to its overturn by the Romans.